2007
DOI: 10.1016/j.ccr.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics Analysis Reveals Silencing of β-Adrenergic Signaling by Polycomb in Prostate Cancer

Abstract: The Polycomb group (PcG) protein EZH2 possesses oncogenic properties for which the underlying mechanism is unclear. We integrated in vitro cell line, in vivo tumor profiling, and genome-wide location data to nominate key targets of EZH2. One of the candidates identified was ADRB2 (Adrenergic Receptor, Beta-2), a critical mediator of beta-adrenergic signaling. EZH2 is recruited to the ADRB2 promoter and represses ADRB2 expression. ADRB2 inhibition confers cell invasion and transforms benign prostate epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
225
0
15

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(247 citation statements)
references
References 42 publications
7
225
0
15
Order By: Relevance
“…38,39 Yu et al demonstrated that EZH2 may mediate increased invasiveness and metastasis by silencing several downstream targets in addition to E-cadherin, including the adrenergic receptor (ADR) ADRB2. 40 Tan et al identified 3-deazaneplanocin A (DZNep), which is a small molecule that inhibits the expression of PRC2 complex proteins containing EZH2 and induces apoptotic cell death together with histone deacetylase (HDAC) inhibitors in cancer cells, but not in normal cells. 41 Taken together with high expression of EZH2 in NSCLC cells and its association with aggressive phenotypes, PRC2 inhibitors like DZNep, which, together with HDAC inhibitor, pharmacologically reverses cancer-associated epigenetic gene repression, may provide potent therapy for NSCLC.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%
“…38,39 Yu et al demonstrated that EZH2 may mediate increased invasiveness and metastasis by silencing several downstream targets in addition to E-cadherin, including the adrenergic receptor (ADR) ADRB2. 40 Tan et al identified 3-deazaneplanocin A (DZNep), which is a small molecule that inhibits the expression of PRC2 complex proteins containing EZH2 and induces apoptotic cell death together with histone deacetylase (HDAC) inhibitors in cancer cells, but not in normal cells. 41 Taken together with high expression of EZH2 in NSCLC cells and its association with aggressive phenotypes, PRC2 inhibitors like DZNep, which, together with HDAC inhibitor, pharmacologically reverses cancer-associated epigenetic gene repression, may provide potent therapy for NSCLC.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%
“…Loss of ADRB2 leads to the enhanced cell invasion and transformation of benign prostate epithelial cells. 14 Cancer gene silencing without DNA hypermethylation restoration of DACT3 provides a therapeutic strategy for controlling Wnt signaling pathway in colon cancer, which is different from the current efforts focusing on direct interference with TCF/β-catenin-mediated transcriptional activation in cancer cells. 16,17 Hence, the discovery of SAM hydrolase inhibitor DZNep as histone methylation inhibitor, together with classical DNA methylation and histone deacetylase inhibitor (HDACi) inhibitor, has made it possible to perturb multiple epigenetic process in a given model system and has been shown to be very useful tool to understand the complexity of epigenetic mechanism and to facilitate the discovery of tumor suppressors that are silenced through alternative mechanism other than DNA methylation (Fig.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] Mechanistically, the oncogenic function of EZH2 has been attributed to associated histone H3 with trimethylated lysine 27 (H3K27Me3), leading to transcriptional repression of tumor suppressor genes, including p16(INK4a) and p19(ARF), 26 E-cadherin, 19 adrenergic receptor-b2, 27 RUNX3, 20 p57 (also called CDKN1C), 21 Bim 28 and DAB2IP. 23,24 As such, EZH2 is emerging as a crucial regulator of cell fate by affecting multiple signaling pathways.…”
mentioning
confidence: 99%